Modern implementations of contrastive linguistic methods in linguistic analysis - Rehila , Kashgarli (The Lingua Spectrum, 2024)
This article examines contemporary methods of contrastive linguistics in language studies, highlighting how its theoretical foundations have evolved to accommodate modern research tools and interdisciplinary approaches. Drawing on pivotal scholarly perspectives, the study addresses the benefits and limitations of contrastive linguistics in areas such as foreign language education, translation, and cross-cultural communication. It explores the integration of corpus-based techniques, cognitive linguistics, and technology-driven applications, showcasing how contrastive analysis now transcends traditional boundaries to enrich linguistic research, teaching methodologies, and practical language applications.